TEACHER FLEXIBILITY IN APPLYING THE AIR LEARNING MODEL TO OVERCOME SLOW LEARNERS IN MADRASAH - Mudarris, Badrul; Nu'man, Agus; Wahyuni, Dewi; Onia, Saifaldin Idris (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
TProblems that occur in MTs Zainul Anwar precisely in class VII students have the characteristics of being difficult to absorb information as a whole due to limited cognitive abilities like poor thinking skills, difficulty with thinking and memory, and uncontrollable the emotion. The purpose of this study is to describe teachers' flexibility in overcoming the slow learner class VII MTs Zainul Anwar through the Auditory, Intellectually, And Repetition model. This research uses qualitative research methods with case study research. Analysis of the data used is the Miles and Huberman Interactive analysis model. The results showed. The teacher's flexibility in applying the AIR learning model is the teacher's efforts through adjustment, technical assistance (additional learning) with a mind mapping, remedial education, and a continuous evaluation with self-monitoring techniques. So, with the teacher's flexibility in applying the AIR learning model, he overcame the slow learner class VII MTs Zainul Anwar. Teachers can use the AIR learning model by using additional classes to make it easier for students to understand the learning material. In addition, it can develop student competence both cognitively and effectively to help improve student learning outcomes.